The Neural Correlates of the Clock-Drawing Test in Healthy Aging - Talwar, Natasha A.; Churchill, Nathan W.; Hird, Megan A.; Pshonyak, Iryna; Tam, Fred; Fischer, Corinne E.; Graham, Simon J.; Schweizer, Tom A. (Frontiers in Human Neuroscience, 2019)
Importance: The clock-drawing test (CDT) is an important neurocognitive assessment tool, widely used as a screening test for dementia. Behavioural performance on the test has been studied extensively, but there is scant literature on the underlying neural correlates. Purpose: To administer the CDT naturalistically to a healthy aging population in an MRI environment, and characterize the brain activity associated with test completion. Main Outcome & Measure: Blood-oxygen-level dependent (BOLD) functional MRI was conducted as participants completed the CDT using novel tablet technology. Brain activity during CDT performance was contrasted to rest periods of visual fixation. Performance on the CDT was evaluated using a standardized scoring system (Rouleau score) and time to test completion. To assess convergent validity, performance during fMRI was compared to performance on a standard paper version of the task, administered in a psychometric testing room. Results: Study findings are reported for thirty-three cognitively healthy older participants aged 52 to 85. Activation was observed in the bilateral frontal, occipital and parietal lobes as well as the supplementary motor area and precentral gyri. Increased age was significantly correlated with Rouleau scores on the clock number drawing (R2) component (rho = -0.55, p < 0.001); the clock hand drawing (R3) component (rho = -0.50, p < 0.005); and the total clock (rho = -0.62, p < 0.001). Increased age was also associated with decreased activity in the bilateral parietal and occipital lobes as well as the right temporal lobe and right motor areas. Conclusion & Relevance: This imaging study characterizes the brain activity underlying performance of the CDT in a healthy older aging population using the most naturalistic version of the task to date. The results suggest that the functions of the occipital and parietal lobe are significantly altered by the normal aging process, which may lead to performance decrements.